2017
DOI: 10.1371/journal.ppat.1006551
|View full text |Cite|
|
Sign up to set email alerts
|

Persistent mycobacteria evade an antibacterial program mediated by phagolysosomal TLR7/8/MyD88 in human primary macrophages

Abstract: Pathogenic mycobacteria reside in macrophages where they avoid lysosomal targeting and degradation through poorly understood mechanisms proposed to involve arrest of phagosomal maturation at an early endosomal stage. A clear understanding of how this relates to host defenses elicited from various intracellular compartments is also missing and can only be studied using techniques allowing single cell and subcellular analyses. Using confocal imaging of human primary macrophages infected with Mycobacterium avium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 77 publications
6
27
0
Order By: Relevance
“…Thus, we investigated whether the increased kinetic of Mtb targeting to phagolysosomes was due to the differential activation of hLECs by Mtb WT and mutants. We monitored the activation of NF-kB (p65) and IRF-1 after infection of hLECs with Mtb WT, Mtb ΔPDIM and Mtb ΔPDIM∷PDIM by confocal microscopy as previously shown [ 40 , 41 ]. We found that after 24 h of infection, Mtb induced NF-kB activation, as measured by translocation of p65 into the nucleus but this activation was not significantly different between Mtb WT and the mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we investigated whether the increased kinetic of Mtb targeting to phagolysosomes was due to the differential activation of hLECs by Mtb WT and mutants. We monitored the activation of NF-kB (p65) and IRF-1 after infection of hLECs with Mtb WT, Mtb ΔPDIM and Mtb ΔPDIM∷PDIM by confocal microscopy as previously shown [ 40 , 41 ]. We found that after 24 h of infection, Mtb induced NF-kB activation, as measured by translocation of p65 into the nucleus but this activation was not significantly different between Mtb WT and the mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory responses are central in controlling infection and we have previously shown that negative regulation of inflammatory responses by Keap1 or by depletion of Toll-like receptor (TLR)-signaling facilitates intracellular replication of Mav in human primary macrophages (2830). We therefore performed a broad systematic screen on the early expression of inflammatory genes to identify changes in immune stimulatory properties that could explain the change in survival.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of IL-1β were highly variable in our experiments. Efficient IL-1β production requires that mycobacteria come in contact with the cytosol and since Mav is not present in the cytosol (30), this could explain the varying results. The ability to activate host defenses by Mav has previously been shown to vary between Mav isolates, and down-regulation of pro-inflammatory cytokines is believed to promote survival of the bacterium (12, 18, 45).…”
Section: Discussionmentioning
confidence: 99%
“…Efficient IL-1β production requires that mycobacteria come into contact with the cytosol, and since M. avium is not present in the cytosol (32), this could explain the various results. The ability of M.…”
Section: Discussionmentioning
confidence: 99%